2021
DOI: 10.1007/s43477-021-00009-0
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Delivery of Functional Family Therapy Around the World During a Global Pandemic

Abstract: This paper describes accommodations that were implemented to support the global delivery of Functional Family Therapy (FFT) in community-based settings during COVID-19. FFT is an evidence-based family therapy that has been used with youth and families in juvenile justice, child welfare, mental health, and school settings. FFT LLC, an organization that disseminates FFT into community settings, currently supports over 350 community-based agencies that deliver FFT globally. Using the implementation framework arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…Yet receiving a mix of remote and in-person was related to more intensive treatment than mainly in-person therapy. Previous research on FFT did not find any difference regarding treatment length and number of sessions between 2019 and 2020 (Robbins & Midouhas, 2021 ).…”
Section: Discussionmentioning
confidence: 68%
“…Yet receiving a mix of remote and in-person was related to more intensive treatment than mainly in-person therapy. Previous research on FFT did not find any difference regarding treatment length and number of sessions between 2019 and 2020 (Robbins & Midouhas, 2021 ).…”
Section: Discussionmentioning
confidence: 68%
“…This may have made it difficult for victims to know where to access help. 8 , 9 Second, victims of IPV or CAN may have been reluctant to seek help due to fears of: (1) contracting the virus by accessing health services, or (2) the perpetrator discovering the victim's attempts to seek help. Kourti et al’s review further suggested that increased proximity of perpetrators to victims under pandemic health restrictions such as work-from-home requirements may have increased coercive control and prevented victims’ help seeking.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,6,4 These restrictions increased the risk for mental health concerns, isolation, loneliness, economic vulnerability, job loss, and business closures and failures that heavily impacted families. 6 While many families 7 and relevant support systems 2,3,8,9 adapted to the pandemic over time, impacts may have been greatest in the first year of the pandemic, and potentially contributed to increased family violence, specifically intimate partner violence (IPV) and child abuse and neglect (CAN). 2,8,10 Pre-pandemic, 30% of women aged 15 and over experienced IPV during their lifetimes, with regional variation ranging from a low of 16% in East Asia to a high of 65% in Sub-Saharan Central Africa.…”
Section: Introductionmentioning
confidence: 99%
“…However, research is limited on the feasibility of using VCT to deliver family therapeutic interventions to this population [11][12][13]. While the use of VCT is not new to the field of family therapy, most studies have examined the feasibility and effectiveness of interventions that primarily target parenting skills for youth with specific mental health problems (eg, [14][15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%